Porous PVDF/PANI ion-exchange membrane (IEM) modified by polyvinylpyrrolidone (PVP) and lithium chloride in the application of membrane capacitive deionisation (MCDI) - Waye Zhang (Water Science and Technology, 2018)
In this work, polyvinylidene fluoride (PVDF)/polyaniline (PANI) heterogeneous anion-exchange membranes filled with pore-forming agents polyvinylpyrrolidone (PVP) and lithium chloride were prepared by the solution-casting technique using the solvent 1-methyl-2-pyrrolidone (NMP) and a two-step phase inversion procedure. Key properties of the as-prepared membranes, such as hydrophilicity, water content, ion exchange capacity, fixed ion concentration, conductivity and transport number were examined and compared between membranes in different conditions. The pore-forming hydrophilic additives PVP and lithium chloride to the casting solution appeared to improve the ion-exchange membranes (IEMs) by increasing the conductivity, transport number and hydrophilicity. The effects of increasing membrane drying time on the porosity of the as-prepared membranes were found to lower membrane porosity by reducing membrane water content. However, pore-forming agents were found to be able to stabilise membrane transport number with different drying times. As-prepared PVDF/PANI anion-exchange membrane with pore-forming agent is demonstrated to be a more efficient candidate for water purification (e.g. desalination) and other industrial applications.